Effects of desflurane, sevoflurane and isoflurane on pulmonary shunt in dogs during spontaneous ventilation - Nunes,N. (2003)
The aim of this study was to compare the effects of desflurane, sevoflurane and isoflurane on pulmonary shunt in dogs during spontaneous ventilation. General anesthesia was induced in 30 healthy, adult, mongrel dogs by intravenous administration of propofol. The animals were separated into three groups of 10 dogs each and submitted to general inhalation anesthesia with 1.5 MAC of desflurane (G1), sevoflurane (G2) and isoflurane (G3). Arterial blood was collected by puncture of the right femoral artery, and mixed blood was collected by introducing a Swan-Ganz catheter into the pulmonary artery. These samples were used to determine the parameters employed for calculation of the intrapulmonary shunt. Measurements began at 20min after orotracheal intubation and were repeated every 20min, totaling six measurements. Means were compared by the Student t-test (P£ 0.05). Desflurane led to a higher shunt than sevoflurane and isoflurane at 40 and 60min. At 80min, the mean values obtained for desflurane were higher than those obtained for isoflurane, while at 100min the values observed for dogs anesthetized with desflurane were higher than those obtained with sevoflurane. Desflurane caused respiratory depression by reducing PaO2, and a higher percentage of intrapulmonary shunt than isoflurane and sevoflurane.